1984
DOI: 10.1002/bjs.1800710211
|View full text |Cite
|
Sign up to set email alerts
|

Laser recanalization of obstructing foregut cancer

Abstract: Palliative treatment of upper gastrointestinal tract obstruction was undertaken by endoscopic laser therapy in 6 patients with carcinoma of the oesophagus or stomach. All had dysphagia for solids on admission and were considered unsuitable for surgery or radiotherapy. Three were in sites unsuitable for placement of an endoscopic prosthesis. The tumours occluded up to 90 per cent of the lumen (2 squamous and 4 adenocarcinomas). Treatment was carried out under direct vision, the laser wave guide being passed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…[10][11][12][13] About 20% of patients complain of chest pain with a burning sensation during or after high-power laser therapy. 1,4,9,19 Our study and other reports 10,25 found that patients had less pain with a low-power contact laser. Acute perforation was a severe complication in 4% of patients receiving high-power laser therapy.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…[10][11][12][13] About 20% of patients complain of chest pain with a burning sensation during or after high-power laser therapy. 1,4,9,19 Our study and other reports 10,25 found that patients had less pain with a low-power contact laser. Acute perforation was a severe complication in 4% of patients receiving high-power laser therapy.…”
Section: Discussionsupporting
confidence: 46%
“…The effective rate of palliative treatment of malignant stenosis varies from 80% to 100%. [1][2][3][4][5][6][7][8][9][19][20][21][22][23][24] The degree of penetration and the course of destruction of GI tumors by high-power noncontact laser or electrical surgery cannot be precisely predicted. [10][11][12][13]25 The preliminary outcome of laser treatment with the low-power contact method has been, encouragingly, as effective as that of high-power laser treatment, with a low risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are also intensively counseled to remain out of reflected or direct sunlight for 1 month as such exposure could lead to very serious sunburn reactions. At 1 month, patients can carefully test their skin reaction to sunlight over [5][6][7][8][9][10][11][12][13][14][15] minute intervals and if no sunburn occurs, exposure to sunlight is permitted.…”
Section: Esophageal Cancermentioning
confidence: 99%
“…Feeding, therefore, becomes a major problem. Current therapy includes endoscopic intubation [9], laparot omy for tumor bypass, feeding gastrostomy or feeding jejunostomy, and laser recanaliza tion [11].…”
Section: Introductionmentioning
confidence: 99%